PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN KONSUMEN PADA BAGIAN GENERAL REPAIR PT. NASMOCO KALIGAWE - M. Boing Norta Ellyandi; Sri Suryoko (Universitas Diponegoro, 2018)
It has become a company goal to make consumers feel satisfied so they can win the competition. In order to fulfill customer satisfaction, the company must be able to improve the quality of service and build a good corporate image in the eyes of customers. This research was conducted because of the expected target in the general repair of PT. Nasmoco Kaligawe during the 2015 to 2017 period has not been achieved and has fluctuated, so it is necessary to know how the influence of service quality and company image on customer satisfaction. This study aims to determine the effect of service quality and corporate image on customer satisfaction using the services of General Repair PT. Nasmoco Kaligawe. This research method is explanatory with data collection techniques through questionnaires and interviews. The population in this study is all consumers who use services in the general repair section of PT. Nasmoco Kaligawe when the research was conducted. The sample taken as many as 100 respondents with the sampling technique used was purposive sampling. Analysis of the data used in this study using the SPSS 18.0 program, where previously tested the validity, reliability, correlation coefficient, coefficient of determination, simple and multiple regression analysis, and significance test (t test and F test) first. The results of this study indicate that the quality of service and corporate image partially and simultaneously affect consumer satisfaction using the services of General Repair PT. Nasmoco Kaligawe. The results of this study indicate that the strength of the relationship between service quality and company image to customer satisfaction is strong (r value 0.628). Both independent variables proved to have a positive and significant influence on customer satisfaction. Evidenced by the results of the calculation of the positive regression coefficient of 0.106 for service quality and 0.451 for corporate image. The calculated F value is 31.605 which is greater than F table (3.0892). Based on the results of the study, researchers suggested that PT. Nasmoco Kaligawe can improve the quality of services provided, especially regarding the length of time to work on repairing or servicing cars and queuing for service advisors. As for the company's image, PT. Nasmoco Kaligawe needs to increase awareness with the surrounding environment by realizing corporate social responsibility.